Design and Implementation of a Blockchain-Based Smart Barcode System to Enhance Supply Chain Traceability of Traditional Golok Ciomas Craftsmanship - Solihin; Dodi; Iswandi Idris (Universitas Medan Area, 2026)
Golok Ciomas, a traditional weapon deeply rooted in Indonesian heritage, holds both cultural and economic significance for local micro-enterprises. However, the expansion of its market reach is hindered by limited supply chain transparency, inadequate product traceability, and the absence of authentication mechanisms. This study presents the design and implementation of a smart QR-based tracking system to enhance supply chain visibility and prevent counterfeiting. Employing a mixed-methods approach—combining participatory field observation with web-based software prototyping— framework embeds dynamic QR codes at every production stage, from raw material sourcing to end distribution. Pilot testing was conducted with selected blacksmiths and local traders in Banten Province. The results demonstrate that platform successfully increases information transparency, verifies product authenticity, and expands digital marketing reach. Compared to traditional manual records, the smart barcode platform significantly reduces data fragmentation and facilitates efficient access without requiring high-end infrastructure. This research contributes to the digital empowerment of heritage-based micro-enterprises while preserving product authenticity. Future improvements include blockchain integration and mobile-responsive features to extend usability. Framework serves as a scalable model for other cultural craftsmanship sectors seeking to modernize without compromising their artisanal identity.